Fonología diacrónica del subsistema oclusivo latino según la teoría glotálica: una nueva propuesta (Minerva, 2019)
According to the most accepted theory, the voiced aspirated stops in Indo-European changed first into voiceless aspirated stops and later into fricatives, both in Latin and Greek. The author in this article tries to explain the coming up of such fricatives in Latin, starting from an indo-European system of plosives made up of three series glottal/voiced/voiceless, and without the need of a phase of voiceless aspirated stops, as do even those authors who use a similar system to the one proposed.